Why general jurisprudence is interesting - Dickson, J (Instituto de Investigaciones Filosóficas, UNAM, 2017)
In a recent article entitled, ‘Is General Jurisprudence Interesting?’, David Enoch answers his own question resoundingly in the negative. This article critically examines the character of Enoch’s claim, the presuppositions it rests on, and the way in which he seeks to establish it. Having argued that many of Enoch’s views in this regard hinge on a narrow and idiosyncratic understanding of the questions that general jurisprudence addresses, and of the relations between those questions and many other inquiries concerning the character of law, the article concludes by offering its author’s own vision of what makes general jurisprudence engaging, intriguing, and … well … interesting.